Multi-time Scale Stochastic Optimization for Hybrid AC-DC Distribution Networks with PET Based on E-C-Kmeans Clustering - Sun, Yaobin; Liu, Shourui; Lu, Jiashuo; Du, Yonggang; Zheng, Huankun (2025 4th International Conference on Smart Grid and Green Energy (ICSGGE), 2025)
This paper addresses the uncertainty of distributed power supply in a hybrid AC-DC distribution network with multi-port Power Electronic Transformers (PET). A multi-time scale stochastic optimization model based on E-C-Kmeans clustering is proposed. First, the E-C-Kmeans clustering and reduction model for new energy scenarios is constructed by integrating the CBFSAFODP algorithm (a fast search and density peak discovery algorithm) with the K-means algorithm. Then, the model aims to minimize wind curtailment penalties, operational and maintenance costs of energy storage devices, electricity purchasing costs, and micro gas turbine generation costs. A random optimization operation model for the day-ahead and intra-day scheduling of the hybrid AC-DC distribution network with PET based on E-C-Kmeans clustering is built. Finally, the case study on the hybrid AC-DC distribution network with PET verifies that the proposed model can reduce system operating costs and effectively address the uncertainty in the distribution of renewable energy generation.